Psychological Operations in Digital Political Campaigns: Assessing Cambridge Analytica's Psychographic Profiling and Targeting - Bakir, Vian (Frontiers in Communication, 2020)
This paper explores whether psychographic profiling and targeting married with big data and deployed in digital political campaigns is a form of psychological operations (‘psy-ops’). Informed by studies on deception, coercion and influence activities from propaganda, persuasion, policy making, cognitive psychology, information and marketing scholarship, this proposition is examined and historically grounded in a politically important case study: the actions of now defunct political data analytics and behaviour change company, Cambridge Analytica, in the UK’s 2016 referendum campaign on leaving the European Union. Based on qualitative analysis of documentation in the UK and USA from public inquiries, regulatory investigations, legal proceedings and investigative journalists, as well as on revelations from digital political campaigners and Cambridge Analytica itself, this paper assesses the coercive and deceptive nature of Cambridge Analytica’s psychographic profiling and targeting, concluding that it is a form of psy-ops. Observing the social unacceptability of such digital campaigning practices (ascertained from national surveys in the US, UK and globally), this paper discusses the adequacy of measures since put in place to eliminate the risk of further psy-ops in digital political campaigning. It ends by elucidating areas in urgent need of further research.